2014
DOI: 10.1016/j.envpol.2014.03.025
|View full text |Cite
|
Sign up to set email alerts
|

Lead isotopic compositions of ash sourced from Australian bushfires

Abstract: a b s t r a c tThis study identifies natural and industrial lead remobilized in ash deposits from three bushfires in relatively pristine areas of Australia in 2011 using lead isotopic compositions ( Pb). Lead concentrations in the ash ranged from 1 to 36 mg/kg, bracketing the range of lead (4e23 mg/kg) in surface soils (0e2 cm), subsurface (40e50 cm) soils and rocks. The lead isotopic compositions of ash and surface soil samples were compared to subsurface soils and local bedrock samples. The data show that ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 40 publications
(15 citation statements)
references
References 29 publications
0
15
0
Order By: Relevance
“…The remobilisation of historic Pb deposits in wildfire ash has also been documented in Australia. The release of Pb during wildfire events and the redistribution of environmental contaminants have received increasing research interest in recent years (Kristensen and others, 2014; Kristensen and others, 2017). Therefore, ( 206 Pb/ 207 Pb) Ant was set to 1.134 based on the average of the results from Australia, including aerosol and wildfire sources (1.139 for aerosols and 1.129 for wildfires; Kristensen and others, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…The remobilisation of historic Pb deposits in wildfire ash has also been documented in Australia. The release of Pb during wildfire events and the redistribution of environmental contaminants have received increasing research interest in recent years (Kristensen and others, 2014; Kristensen and others, 2017). Therefore, ( 206 Pb/ 207 Pb) Ant was set to 1.134 based on the average of the results from Australia, including aerosol and wildfire sources (1.139 for aerosols and 1.129 for wildfires; Kristensen and others, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…Also included in the plot are the ranges of natural and industrial lead isotopic ratios of aerosols collected from Central-South Chile (Böllhofer and Rosman 2000;De Vleeschouwer et al 2008) reported at sublethal blood Pb (PbB) levels that were previously considered harmless (Wheeler and Brown 2013). Although the amounts of trace elements mobilized in Patagonia by wildfire are relatively small compared to those mobilized in more industrialized regions (e.g., Kristensen et al 2014;Odigie and Flegal 2014), increased remobilization of Pb by wildfire could become problematic.…”
Section: Potential Environmental and Health Implicationsmentioning
confidence: 99%
“…The latter include a recent study in the relatively unpopulated and relatively pristine Santa Barbara area north of Los Angeles [25] and a similar study in Australia [26]. In contrast to those studies, this study was conducted in the Angeles National Forest, which is adjacent to the Los Angeles Metropolitan area, which has a population of ∼17 million [27], has many large sources of industrial contaminants [28][30], and ranks as one of the nation’s most contaminated metropolitan areas [31].…”
Section: Introductionmentioning
confidence: 99%